ION-EXCHANGE THIN-LAYER CHROMATOGRAPHY OF ELEMENTS. 2. Study of the complexation of Re (VII), Mo (VI), V (V) and W (VI) ions in organic acid solutions (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
Complexation of Re(VII), Mo(VI), V(V) and W(VI) ions on «Fixion-50» cationite fixed layers has been studied using oxalic, tartaric and citric acids solutions as mobile phases. The row of relative stability of complexes of indicated ions with appropriate acids has been revealed. The obtained date of using the two versions of ion-exchange chromatography (column and thin-layer) do not differ, and it confirms their reliability and accuracy. It is expedient to apply the ion-exchange thin-layer chromatography method more widely for the study of complexation in solutions, because this version of chromatography is more express and does not suppose the use of complicated and expensive instruments.
Keywords: complexation; «Fixion-50»; oxalic, tartaric and citric acids; ion-exchange thin-layer chromatography method; Re(VII), Mo(VI), V(V) and W(VI) ions